Sleep behavior and daily activity levels in people with metabolic syndrome: effect of 1 year of metformin treatment - Bruno, Eleonora; Mulè, Antonino; Galasso, Letizia; Castelli, Lucia; Baldassari, Ivan; Oliverio, Andreina; Venturelli, Elisabetta; Berrino, Franco; Montaruli, Angela; Roveda, Eliana; Pasanisi, Patrizia (Frontiers in Nutrition, 2023)
Impaired sleep and low daily activity levels increase the risk of developing Metabolic Syndrome (MS). Metformin (MET), an insulin sensitiser drug, is effective in regressing MS and has been recently studied as adjuvant agent for managing sleep disorders. The present study aimed to assess whether a 1700 mg/day of MET treatment modifies sleep and daily activity levels evaluated by Rest-Activity circadian Rhythm (RAR), which is the expression of 24 hours of spontaneous activity parameters, in people with MS. 133 subjects with MS, randomised into MET (n=65) or placebo (PLA, n=68) group, underwent a clinical/anthropometric examination and carried out a continuous 7-day actigraphic monitoring to investigate sleep and RAR parameters at baseline and after one year of intervention. After one year of intervention, 105 subjects were analysed. The MET group showed greater anthropometric and metabolic improvements compared to placebo, with a significant reduction of weight (p=0.01), body mass index (p=0.01), waist circumference (p=0.03) and glucose (p<0.001). About sleep parameters, MET group showed a significant increase in actual sleep time (p=0.01) and sleep efficiency (p=0.04) compared to placebo. RAR parameters reported no significant changes. Our study suggests that MET might be used as adjuvant treatment for sleep disorders in people with MS.